Kajian Literature : Pengaruh Independensi, Profesionalisme Dan Akuntabilitas Auditor Terhadap Kualitas Audit - Siti Rodiah; Atika Fitriani; Nadia Fitri Ramadani; Sarifah Aini Hasibuan; Melki Wijaya (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Previous studies are very important in scientific articles and research. Relevant research is conducted to support theories about identifying influences or correlations between variables. Several elements that affect internal audit quality are discussed in this article, including auditor independence, professionalism, and reliability. The purpose of this article is to gain an understanding of how auditor independence, professionalism, and accountability affect internal audit quality. The results of this study show that: 1) Independence does not affect internal audit quality, 2) Professionalism affects internal audit quality and 3) Auditor credibility affects internal audit quality